PPH Final Bagi UMKM di Kecamatan Medan Sinembah - Yuni Shara; Debbi Chyntia Ovami; Junita Putri Rajana Harahap (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Community service aims to make the business community have knowledge about the Final PPH for UMKM such as how to register, calculate the tariff, when to apply and report it. The method applied is classical and individual. This approach method in the form of lectures and practice. Individual approach is carried out during practice in the form of income calculation until the final PPH reporting. The location of this service is Medan Sinembah Village, Tanjung Morawa Sub-district, Deli Serdang Regency, SUMATERA UTARA.. As a result of this activity, UMKM entrepreneurs can calculate, pay the final PPH and report their tax reports properly and on time and improve the welfare of family life in the village of Medan Sinembah